The color image in Khaled Al-Kateb’s poetry (Journal of the College of Basic Education, 2024)
The poetic image represents one of the basic components in the production of literary work, but its use differs from one poet to another, and with the change in the system of the Arabic poem and its lexicon, it also had to change in its nature and components of its composition. “The image in poetry is the (artistic form) that words and expressions take after For the poet to organize it in a special graphic context to express an aspect of the complete poetic experience in the poem.” Words and phrases are the first material that the poet relies on in building his poetic images and formulating their artistic form.